Estudio de factibilidad para la creación de una empresa productora y comercializadora de bebidas saborizadas y endulzadas con panela en la ciudad de Armenia (2015)
The research "Feasibility study for the creation of a company dedicated to the production and marketing of flavored drinks and sweetened with brown sugar in the city of Armenia" is from an identified problem that is present in Colombia and worldwide that is obesity and associated with this, such as diabetes, cardiovascular problems, bone decalcification, among others, all these chronic diseases considered; this is given by the high consumption of sugary drinks such as soft due to its high content of refined sugar and other unhealthy components are responsible for such conditions. To counter this, the idea is to produce a drink that is sweetened with natural sugar panela containing vitamins, minerals and antioxidants, to contribute to a healthy diet. For this corresponding to a market survey analysis, technical, organizational, legal, environmental and financial variables that must be taken into account in the development and implementation thereof it is presented, that as a result the project is feasible in a real scenario, but only if it occurs on a large scale, that is, the project requires a large investment to be profitable.